The effects of lipopolysaccharide-induced endogenous hyperthermia and different antipyretic treatment modalities on rat brain - Aydin, M.; Kislal, F. M.; Ayar, A.; Demirol, M.; Kabakus, N.; Canatan, H.; Yoldas, T. K. (Comenius Univ, 2011)
Background: In the present study, the effects of fever and hyperthermia, and different anti hyperthermia treatment modalities on the brain by was investigated by using experimental animal model Materials and methods: Endogenous hyperthermia (41 degrees C) was induced by lipopolysaccharide (LPS) injection, and the signs of probable neuronal damage were evaluated by healthy, necrotic and apoptotic cells, and heat-shock proteins (HSP 27 and HSP 70) in cerebral cortex, cerebellum and hypothalamus. The animals were treated with widely used treatment modalities for high fever in pediatric practice, namely hypothermia, dexamethasone, paracetamol and diclofenac, and their effect on the hyperthermia-induced brain changes were evaluated. Results: Generalized seizure was observed in fifteen rats of which rectal temperature achieved 41 degrees C (15/36, 41 %); five of them died on second day (5/15, 33 %). LPS-induced endogenous hyperthermia;. (i) caused significant increase of necrotic cells in cerebral cortex and cerebellum and apoptotic cells in all three regions (p<0.05), (ii) caused significant decrease of healthy cells in cerebral cortex (p<0.05), and (iii) no significant change of HSP 27 and 70 in all three neuronal locations (p>0.05). For the treatment modalities applied; (i) paracetamol had an effect of increasing the healthy cell count in cerebral cortex and hypothalamus and decreasing the necrotic cell count in cerebellum and hypothalamus (p<0.05). Conclusion: The neuronal tissue in different regions of brain can show various degrees of damage in response to endogenous hyperthermia and the applied medications have varying degree of protection (Tab. 3, Fig. 6, Ref. 44). Full Text in free PDF www.bmj.sk.
Keywords: lipopolysaccharide; hyperthermia; rat; brain damage; treatment